Toward Evidence Based Practice. Issue 3 (May 2015) - Lipman, Terri H.; Oweis, Arwa; Lewis, Judith A.
<x xml:space="preserve">Abstract</x> Experts suggest how 6 research articles can be used in nursing practice.